Helyi adók rendszere és alkalmazása az egyes önkormányzatoknál - Puskásné Bruckner Tímea (2017)
The topics of my thesis are the system and application of local taxes at certain local gov-ernments, as well as the presentation of my own research. In the first of half of my thesis I describe the history and significance of taxation, and its place in Hungary; then I present the general rules of local taxes, and within that, the concept of local taxes according to several definitions, as well as the purpose of intro-ducing local taxes, the characteristics of local taxes, the types and kinds of local taxes. In addition, I describe who may be subject to local taxes in general, and which entities, per-sons are entitled to exemption. The next chapter includes a brief description of the regula-tions applicable to the introduction of local taxes, in respect of which the act on local taxes stipulates only a notification rule. Afterwards, you may read about the rules and principles determining the assessment of the tax, as well as the characteristics thereof. My thesis will show the multitude of factors affecting the introduction of local taxes. Then, a greater part describes the types and kinds of local taxes, separately. My the-sis presents the tax base, taxable person, tax liability, tax rate, tax discount and the exemp-tion specified by law for each category of tax. In addition, I mention the vehicle tax brief-ly, because although it is not a local tax but a ceded central tax, it is still a tax-like income, and it is the task of the tax authority of the local tax to collect it. Since the title of my thesis includes the word “application”, therefore I compared local taxation regulation practice of 9 settlements (which belong to two Joint Municipali-ties) in respect of a five-year period. In course of the comparison, I carried out the analysis also according to categories of tax. I tried to illustrate the collected tax revenues and other indicators supporting the comparison with charts and different diagrams. One of the important sources of income of local governments is the local tax reve-nue, thus I believe it is important to demonstrate the development of the total revenue in respect of the settlements examined, as well as the development of the local tax revenues and the ratio thereof to the total revenue. I carried out a questionnaire research among the decision-makers of the villages; through the questionnaires I got a picture of the system and application of the local taxes, as well as the possible future intentions and plans. I col-lected the data and compiled a summary on the results. In course of the comparison I con-cluded that in case of these small settlements, the rate of local tax revenues is not signifi-cant, however, local tax revenues still constitute one of the most important sources of in-come for these settlements, using which they are able to finance their operational expendi-tures, as well as realize any possible development.